Penalising parents for failure to vaccinate children: Analysis from other countries - Khairun-Nisaa, Asari; Maheran, Makhtar; Farhanin, Abdullah Asuhaimi; Nur Amani, Pauzai (2018)
The vaccination of children has proved to be one of the most effective and important health interventions in battling infectious diseases. Yet despite the phenomenal success of childhood vaccination, a growing number of parents in Malaysia choose not to vaccinate their children each year. Hesitation towards vaccination especially among parents has resorted to certain countries in enforcing compulsory childhood vaccination laws. A parent’s decision not to vaccinate a child may place others at risk if the child becomes infected and exposes others to the disease. Thus, an issue arose as to should we impose a legal duty on parents to vaccinate their child? This paper focuses on the imposition of liability on parents for failure to vaccinate children. The main discussion will revolve around the requirement of compulsory vaccination of children and the practices of other countries on penalizing parents for non-vaccination of their children. This paper seeks to examine the alternative of enforcing compulsory vaccination for children in Malaysia by looking at the comparative approach taken in Australia. The authors adopted qualitative research method to gather data in writing this paper. It is found that it is not easy to implement compulsory vaccination, mainly due to the conflicting rights of parents to rear his or her child according to his or her own standards, the right of the child to receive health care, and the rights of the public to be protected from vaccine-preventable infectious disease. Most countries resort to other preferable alternatives such as financial incentives and quasi-mandatory interventions instead of penalizing parents for refusal to vaccinate their children.